The skidding component of the mixed peat swamp logging system - Manikam, Doraisingam (Forestry Department Peninsular Malaysia, 1983)
A study was conducted in the Mixed Peat Swamp Forests of Sarawak in order to quantify the skidding component of the logging system. Both the one-and two-skid team crews were studied. The skidding component comprises five basic work elements, namely outhaul, load, sling,.inhaul and unload. Load and inhaul were the largest work elements accounting for 30 percentor more of the basic cycle time. The basic cycle time ranged from 63 - 88 percent of the total cycle time depending upon the crew performance. Crew performance has been quantified by a parameter called skidding potential. Skid distance and log weight were found to be significant variables accounting for 61 percent of the variation in basic cycle time. However, crew aggressiveness and the variability in skidding potential can counteract the effect of skid distance and log weight on cycle time. The incidence of delays and their frequency may also be attributed to these factors. It is concluded that skid distance, log weight and crew aggressiveness control the skidding productivity of the system.